PENGARUH SUBSTITUSI BIJI JALI (Coix lacryma-jobi L.) TERHADAP KOMPOSISI PROKSIMAT, SERAT, DAN FENOL PADA TEMPE KEDELAI - Nadiya Rahmah Qurnaini (2021)
Coronary Heart Disease (CHD) can be caused by several factors, one of which is dyslipidemia. Jali is a food that contain antidyslipidemic bioactive components, that is dietary fiber and phenols. The purpose of this research is to analyze the effect of substitution of jali seed (Coix lacryma-jobi L.) on the composition of proximate, fiber, and phenol content of soybean tempe and choose the best formula. This research used an experimental method with a one-factor Completely Randomized Design (CRD) with two repetitions. The factor is formula of soybean tempe with jali seed substitution, that is F1 60:40, F2 50:50, and F3 40:60. The composition of proximate, fiber, and phenol content were analyze using ANOVA and DMRT tests, while the organoleptic test was analyze using Kruskal Wallis and Mann-Whitney tests. The results of the ANOVA test showed that there was no significant effect (p> 0.05) of the three formulations on water, ash, fat, carbohydrate, and crude fiber content, while there was a significant effect (p <0.05) of the three formulations on protein, dietary fiber, and phenol content. The results of the Kruskal Wallis test showed that there was no significant effect (p> 0.05) of the three formulations on the level of preference for the color, aroma, and taste, while there was a significant effect (p <0.05) of the three formulations on the level of texture preference. The selected formula obtained from the Exponential Comparison Method (ECM) by comparing the water, ash, protein, fat, carbohydrate, dietary fiber, crude fiber, phenol content and the level of preference for the color, texture, aroma, and taste is F3 with the ratio of soybean and jali seed is 40:60. The serving size for the selected formula is 50 g with 3,07% energy, 8,3% protein, 0,33% fat, 3,39% carbohydrates, and 79,38% content dietary fiber from general category of ALG. The selected formula of soybean tempe with jali seed substitution has a claim high of dietary fiber and fat free.